Valuation of Quarterly Stock Prices: Applying Ethical Principles to Discounted Cash Flow Method - Boularhmane, Ilham; Aboulaich, Rajae (International Journal of Economics and Financial Issues, 2016)
Even though companies’ valuation techniques have evolved and have been developed into more sophisticated methods, there is still a big dilemma in the investing world about finding the price of a company. Our research focus on finding the price for a company’s stock by using ethical principles in addition to economical foundation. This paper covers the merger of economic, financial, and ethical factors included in the model and resulting in an intrinsic price using a modified discount cash flow (MDCF) method. Presentation of the model’s results were discussed to compare the MDCF stock value to the actual market price. Our inference shows that incorporating ethical principles, like using real economy factors instead of interest rate and using paid taxes in a valuation model can show a better correlation with stock prices compared to regular DCF model prices for the chosen companies. Such model can be developed as a response to investors’ choice for ethical strategies for stocks selection strategies as well as assets valuation. Keywords: Valuation Method, Socially Responsible Companies, Stock Selection, and Discounted Cash Flow Method. JEL Classifications: G12; G32; M14